Relación entre Pensamiento Repetitivo Negativo (PNR) y la depresión en adultos: revisión aplicada - Cabanillas Villanueva, Patricia Ayelen (2023)
Depression is one of the most prevalent disorders in the world, from the cognitive behavioral approach it has symptoms such as ruminative and negative thoughts. Repetitive Negative Thinking (NRT) is an intrusive, hard to disconnect, and repetitive style of thinking. The objective of this paper is to analyze the relationship between NRP and depression, through a review of research. A search for articles was carried out following the PRISMA guide. Studies that associated NRT with depression in adults (n=10) were selected. All the instruments that measure PNR presented significant reliability, in addition, information analysis tables focused on the relationship between the variables were made. The results indicate that there is a positive and significant relationship between NRT and depression. In addition, the NRT is a mediator variable of depression with other variables; it is a predictor of depression and is positively and significantly related to the worsening of depressive symptoms. Additionally, the general NRT factor has a positive and significant relationship with depression, a comparison of its specific factors (rumination and worry).